2022
DOI: 10.1158/1535-7163.mct-22-0322
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of STRO-002, a Novel Homogeneous ADC Targeting Folate Receptor Alpha, for the Treatment of Ovarian and Endometrial Cancers

Abstract: STRO-002 is a novel homogeneous FolRα targeting antibody drug conjugate (ADC), currently being investigated in the clinic as a treatment for ovarian and endometrial cancers. Here we describe the discovery, optimization, and anti-tumor properties of STRO-002. STRO-002 was generated by conjugation of a novel cleavable 3-aminophenyl hemiasterlin linker-warhead (SC239) to the non-natural amino acid para-azidomethyl-L-phenylalanine (pAMF) incorporated at specific positions within a high affinity anti-FolRα antibody… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…ADC binding to the FcRn receport protects from degradation and has been demonstrated to be an important determinant of efficacy, safety, and pharmacokinetics (PK) [ 36 ]. aFolR ADCs were prepared by conjugating the SC239 DBCO-hemiasterlin drug linker to IgG produced in CFPS using either two-plasmid co-expression or PFLC [ 37 ]. Comparison of the BLI data ( Figure S6 ) and the resulting kinetic constants from fitting with a one-to-one model ( Table 3 ) demonstrate that binding to FcRn at pH 5.8, the physiologically relevant pH, is identical for proteins produced by CFPS, irrespective of the method of LC production.…”
Section: Resultsmentioning
confidence: 99%
“…ADC binding to the FcRn receport protects from degradation and has been demonstrated to be an important determinant of efficacy, safety, and pharmacokinetics (PK) [ 36 ]. aFolR ADCs were prepared by conjugating the SC239 DBCO-hemiasterlin drug linker to IgG produced in CFPS using either two-plasmid co-expression or PFLC [ 37 ]. Comparison of the BLI data ( Figure S6 ) and the resulting kinetic constants from fitting with a one-to-one model ( Table 3 ) demonstrate that binding to FcRn at pH 5.8, the physiologically relevant pH, is identical for proteins produced by CFPS, irrespective of the method of LC production.…”
Section: Resultsmentioning
confidence: 99%
“…STRO-002 is an ADC that contains taltobulin, a synthetic analog derived from hemiasterlin, originally sourced from the marine sponge Hemiasterella minor . Phase I clinical trial for STRO-002 is in progress in ovarian cancer and endometrial cancer patients (NCT03748186, NCT05200364, and NCT05870748) [ 65 ]. E7130, a novel antitumor agent inspired by the natural compound norhalichondrin B [ 66 ], is currently undergoing evaluation in phase I clinical trials of solid tumors (NCT03444701).…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…One such novel ADC targeting FRα is STRO-002. In a study conducted by Li et al, STRO-002 was found to bind to FRα with increased affinity, leading to the avid internalization of the ADC into cells carrying FRα [ 18 ]. After this process occurs, a cytotoxin is released, specifically a tubulin-targeting cytotoxin called 3-aminophenol hemiasterlin, which was seen to significantly reduce tumor growth, particularly when it was combined with platinum- or Avastin-based treatments.…”
Section: Role Of Frα In Ovarian Cancermentioning
confidence: 99%